Cropping Systems and their Diversity in Khulna Region (Bangladesh Rice Journal, 2018)
This study includes the existing cropping pattern, cropping intensity and crop diversity of Khulna region. A pre-designed and pre-tested semi-structured questionnaire was used to collect the information and validated through organizing workshop. Single T. Aman cropping pattern was the most dominant cropping pattern in Khulna region existed in 17 out of 25 upazilas. Boro-Fallow-T. Aman cropping pattern ranked the second position distributed almost in all upazilas. Boro-Fish was the third cropping pattern in the region distributed to 17 upazilas with the major share in Chitalmari, Dumuria, Rupsha, Tala, Kalaroa, Mollahat, Terokhada, Bagerhat sadar, Fakirhat, Rampal and Phultala upazilas. Single Boro rice was recorded as the fourth cropping pattern covered 18 upazilas with the higher share in waterlogged area of Dumuria, Mollahat, Tala, Bagerhat sadar, Fakirhat and Rampal. The highest number of cropping patterns was recorded in Kalaroa (26) followed by Tala (24) and the lowest was reported in Mongla (5). The overall crop diversity index (CDI) for the region was 0.93. The highest CDI was in Tala (0.95) and the lowest in Dacope (0.42). The average cropping intensity (CI) of the Khulna region was 171% with the lowest in Mongla (101%) and the highest in Kalaroa (224%).Bangladesh Rice j. 2017, 21(2): 203-215